Horn fly and face fly control with the Dustacator® combination mineral feeder and livestock dusting device - Mock, Donald E.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Dustacators (combination mineral feeders and livestock dusting devices) were used for four beef herds at Kansas State University in 1985. Loose mineral was supplied in all four Dustacator tubs, which were adjusted to low settings. Permethrin dust had no apparent effect on horn flies. Co-Ral® from two sources and Rabon® provided approximately 65% horn fly reduction during the 53-day test period. The 1986 experiment compared the effects of Dustacator mineral tub height adjustments and loose vs. block mineral. Co-Hal 1% dust from a single source was used in all treatments on two Simmental herds and two Polled Hereford herds. Excellent horn fly control was achieved and maintained except for a temporary increase in horn fly numbers in early September in all treatments. Face fly control was inadequate in all treatments in both years. Use of block mineral was related to reduced mineral consumption and self-application of more insecticide dust. High tub adjustment was related to greater mineral consumption but reduced self-application of insecticide. The degree of fly control was not correlated with amount of insecticide used either on a per-cow or per-herd basis. Simmentals consumed nearly twice as much mineral per head as Polled Herefords, but they used only 20% more insecticide. Including the cost of 1% Co- Ral dust and equipment costs amortized over 5 years, Dustacators provided acceptable horn fly control and some reduction of face fly numbers for $1.62 per cowlcalf pair, plus labor.
Keywords: Beef; Horn fly; Face fly; Dustacator®; Dust; Mineral feeder